Virtual Reality for Virtual Commissioning of Automated Guided Vehicles - Allmacher, Christoph; Dudczig, Manuel; Knopp, Sebastian; Klimant, Philipp (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
The development process of automated guided vehicles (AGV) can be supported by virtual commissioning, which comprises the validation of functionality using a simulation of the AGV. In case of collaborating AGVs, testing their functionalities require the simulation to contain not only the AGV but also a human and an interaction device. Therefore, this paper presents a setup, that integrates a human using motion capturing and emulates a smartwatch as interaction device. Furthermore, the simulation is visualized by a head-mounted display and provides additional information for the test case assessment and analysis. Thus, it enables the virtual commissioning of collaborative AGVs.